2019
DOI: 10.1021/acs.jpcc.9b06106
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Work Function of Carrier Transport Materials with Perovskite on Switchable Photovoltaic Phenomena

Abstract: The hysteresis effect and switchable photovoltaic phenomena in organo-metal halide perovskite have been observed in perovskite solar cells with certain structures and under certain measure conditions. These phenomena were favorably applied to resistive random-access memory and human-brain-mimicking devices, especially using photons as a reading or stress probe apart from using electrical probe. However, the mechanisms causing these effects are not fully understood. In this paper, the perovskite devices with di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 52 publications
1
8
0
Order By: Relevance
“…Rising star semiconducting materials such as organic–inorganic hybrid halide perovskite and antimony selenide are emerging candidates for the next generation photovoltaic devices. , Perovskite solar cells (PSCs) have made great progress, associated with soared power conversion efficiencies (PCEs) in the past ten year. These achievements mainly benefit from the strong light absorption, superior carrier diffusion length, and long carrier lifetime of perovskite materials. , However, undesirable instabilities, such as the light-soaking effect, current hysteresis, and material degradation under operation conditions, seriously inhibit the stable power output and long-term lifetime of PSCs. Since 2014, the anomalous current hysteresis that depends on the scan direction and increment has received great attention. , It was found that preconditioning the solar cell, such as by light soaking or holding at a reverse scan, exhibited favorable photovoltaic characteristics. Experimental achievements have confirmed that the hysteresis mainly originates from ion migration in bulk perovskite, unbalanced carrier transport, and high defects served as recombination centers .…”
Section: Introductionmentioning
confidence: 99%
“…Rising star semiconducting materials such as organic–inorganic hybrid halide perovskite and antimony selenide are emerging candidates for the next generation photovoltaic devices. , Perovskite solar cells (PSCs) have made great progress, associated with soared power conversion efficiencies (PCEs) in the past ten year. These achievements mainly benefit from the strong light absorption, superior carrier diffusion length, and long carrier lifetime of perovskite materials. , However, undesirable instabilities, such as the light-soaking effect, current hysteresis, and material degradation under operation conditions, seriously inhibit the stable power output and long-term lifetime of PSCs. Since 2014, the anomalous current hysteresis that depends on the scan direction and increment has received great attention. , It was found that preconditioning the solar cell, such as by light soaking or holding at a reverse scan, exhibited favorable photovoltaic characteristics. Experimental achievements have confirmed that the hysteresis mainly originates from ion migration in bulk perovskite, unbalanced carrier transport, and high defects served as recombination centers .…”
Section: Introductionmentioning
confidence: 99%
“…Compared with the pristine PtSe 2 substrate, the total shifts of the Pt XPS peaks are 0.3 eV after the deposition of 4Me, which probably originate from the charge redistribution occurring at the 4Me–PtSe 2 interface because of the work function mismatch, resulting in band bending in the 4Me layer. As shown in Figure S2, the UPS and IPES spectra also demonstrate a notable shift of 0.3 eV toward higher binding energy with increasing 4Me thickness, and the shifting is normally a result of energy band bending. In addition, the ionization energy and electron affinity of 4Me can be directly obtained from the onset potentials of the filled and empty states, respectively. As a result, the energy band diagrams of the 4Me–PtSe 2 heterostructure and corresponding CT mechanism are depicted in Figure b.…”
Section: Resultsmentioning
confidence: 97%
“…Since the whole thickness of the BiI 3 layer in the device is set as 1500 Å, the spectra with the BiI 3 layer thickness from 20 to 300 Å represent the atomic status of Bi 4f peaks near the area of the PMMA layer. Within the region close to the PMMA layer, the XPS peaks of Bi 4f 7/2 can obviously be divided by three peaks which are located at 158.75 and 157.00 eV, corresponding to the oxidation state (Bi 3+ ) and metallic state (Bi 0+ ) of bismuth atoms, respectively. , Moreover, not only is the intensity of the Bi metallic states (Bi 0+ ) higher than that of the Bi oxidation states (Bi 3+ ), but it indicates that a large portion of the metallic states (Bi 0+ ) inside the BiI 3 layer can be formed, which enhances the initial formation of conductive filaments inside the area close to the PMMA layer. Thus, the XPS spectra, as shown in Figure a,b, demonstrate that there exist conductive filaments of bismuth metallic states at the interfaces between bismuth iodide and silver electrode.…”
Section: Resultsmentioning
confidence: 99%